Smad anchor for receptor activation nuclear localization during development identifies Layers V and VI of the neocortex. Issue 13 (15th February 2020) - Mestres, Ivan; Einsiedel, Maximilian; Möller, June; Cardoso de Toledo, Beatriz
Abstract: Smad anchor for receptor activation (SARA, zfyve9 ) has been classically observed in early endosomes of different cells types where it regulates vesicular transport of proteins and membrane components. Very few other members of the zinc finger FYVE domain‐containing family ( zfyve ) have different functions other than controlling membrane trafficking. By analyzing SARA localization throughout mouse embryonic brain development, we detected that besides the endosomal localization it also targets neuronal nuclei, specifically of the cortical layers V/VI. These findings were confirmed in human brain organoids. When evaluating neuronal cell lines, we found that SARA accumulates in nuclei of PC‐12 cells, but not Neuro‐2a, highlighting its specificity. SARA functions as a specific marker of the deep cortical layers until the first postnatal week. This temporal regulation corresponds with the final phases of neuron differentiation, such as soma ventral translocation and axonal targeting. In sum, here we report that SARA localization during brain development is temporarily regulated, and layer specific. This defined pattern helps in the identification of early born cortical neurons. We further show that other zfyve family members (FYCO1, WDFY3, Hrs) also distribute to nuclei of different cells in the brain cortex, which raises the possibility that this might be an extended feature within the protein family. Abstract : Smad anchor for receptor activation, besides localizing to early endosomes, exhibits a distinctive nuclear distribution in deep‐layer neurons of the cortex (Layers V and VI). This pattern allows the identification of specific neuronal subpopulations.